2023
DOI: 10.1021/acs.molpharmaceut.2c01062
|View full text |Cite
|
Sign up to set email alerts
|

Polyaspartic Acid-Stabilized CaCO3-Containing In Situ Hydrogel for Protection and Treatment of Gastric Ulcer

Abstract: The lack of effective oral drug delivery systems to treat gastric ulcer is an urgent challenge in clinical practice. Herein, a gastric acid pH-responsive hydrogel of curcumin/sodium alginate/polyaspartic acid@CaCO3 (Cur/SA/PC) was developed for sustained release of Cur, exerting effective protection and treatment of gastric ulcers. The in vitro gelatinization properties and the corresponding gel characteristics of the SA/PC delivery system demonstrated the successful construction of the in situ hydrogel with u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 39 publications
0
0
0
Order By: Relevance
“…Notably, pretreatment with Dex and ODF@Dex markedly reversed the observed decrease in cell viability. Cell migration is a crucial aspect of tissue repair, and H 2 O 2 treatment is known to inhibit the migration of human gastric epithelial cells and HOK cells. , In our study (Figure B, C), pretreatment with Dex and ODF@Dex significantly promoted the migration of HOK cells, increasing the relative migration rate by approximately 45% and 50%, respectively. Previous studies have reported that Dex activates the PI3K/Akt signaling pathway to counteract apoptosis in human fibroblasts and auditory hair cells.…”
Section: Resultssupporting
confidence: 55%
“…Notably, pretreatment with Dex and ODF@Dex markedly reversed the observed decrease in cell viability. Cell migration is a crucial aspect of tissue repair, and H 2 O 2 treatment is known to inhibit the migration of human gastric epithelial cells and HOK cells. , In our study (Figure B, C), pretreatment with Dex and ODF@Dex significantly promoted the migration of HOK cells, increasing the relative migration rate by approximately 45% and 50%, respectively. Previous studies have reported that Dex activates the PI3K/Akt signaling pathway to counteract apoptosis in human fibroblasts and auditory hair cells.…”
Section: Resultssupporting
confidence: 55%
“…Recently, hydrogels have attracted wide attention in biomedical applications due to their biocompatibility and structural versatility [ 132 ]. As promising biological building blocks, M13 phages can be used to construct bioactive materials for biomedical applications [ 133 ].Tian et al [ 134 ] developed a bioactive gel system based on M13 phage by chemical cross-linking.…”
Section: Classification Of Phage-based Delivery Systemsmentioning
confidence: 99%